Experimental and analytical studies on seismic behaviour of precast concrete moment-resisting frames with beam-to-beam connections - Khoo, Jyh Hao. (2008)
In this research, an innovative frame configuration system, whereby the connections are to be relocated on the beam at a distance away from the column faces, has been suggested in attempt to avoid the coincidence with the inherent plastic hinge regions (column face) under seismic conditions.